Who lacks pension knowledge, why and does it matter? Evidence from Swedish retirement savers - Mikael Elinder; Johannes Hagen; Mattias Nordin; Jenny Säve-Söderbergh (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
Recent pension reforms have shifted a larger responsibility towards savers. Individuals therefore need better knowledge of the rules and incentives embedded in the pension system to adequately save and prepare for retirement. In this paper, we use a novel Swedish survey matched with high-quality administrative data to show that many lack, and feel that they lack, such pension-specific knowledge. We also show that the most economically vulnerable groups know the least. Linking pension knowledge to behavior, we find that knowing less is associated with lower preparedness for retirement, even after controlling for financial literacy and subjective knowledge. Moreover, a large majority state the complexity of the pension system, or that they have planned to learn more about pensions but that it just hasn't happened, as reasons for why they do not have sufficient knowledge. That the complexity of the pension system and individuals' proclivity to procrastinate are plausible causal factors for low pension knowledge is supported by analyses showing that individuals with low math skills and procrastination tendencies have lower pension knowledge.
Keywords: H55; D80; D83; 330; bounded rationality; financial literacy; saving; pension system